Influence of Yeast β-Glucan on Cookies Sensory Characteristics and Bioactivities - Umar Bacha; Muhammad Nasir; Sanaullah Iqbal; Aftab Ahmad Anjum (Journal of Chemistry)
β-Glucan is biologically active polysaccharide, ubiquitously found in many grains, bacteria, and fungi and much yeast. The aim of this study was to determine the effect of substituting wheat flour by 1, 2, and 4% yeast isolated β-glucan in cookies on the sensory acceptance, antioxidants, oxidative stability, and quality evaluation which were investigated. According to the results, cookies supplemented at 2% yeast β-glucan were proved satisfactory on sensory quality perspective. During the storage study it was found that cookies made with 2 and 4% β-glucan have effectively (p>0.05) kept the peroxide value (PV) within acceptable range, demonstrating the promising role of β-glucan in deterring oxidative. It is further noted that 2 or 4% β-glucan incorporated cookies assimilated highest absorption spectra, suggesting the retardation in freshness losses, with having minimum microbial loads, showing microbiological safety. β-Glucan fortification in foods is technologically and economically feasible, suggesting that a significant prospect of β-glucan as low-cost food ingredient in formulating cookies at 2% offers exciting new use of β-glucan of yeast origin.